Bioenergy and Employment. A Regional Economic Impact Evaluation - Romero, Carlos; Ernst, Christoph; Epifanio, Daniele; Ferro, Gustavo (International Journal of Sustainable Energy Planning and Management, 2023)
Estimating green energy’s impact on regional economies of developing countries is challenging, owing both to the lack of disaggregated data of non-conventional energy sources at the subnational level and a method to address its participation in the energy matrix. We develop a methodology to solve both problems and apply it to the case of Santa Fe province, Argentina, an important producer of biofuels (biodiesel from soybean and ethanol from maize). To disaggregate the participation of biofuel sectors we combine aggregated sector information with subsector surveys. Once established the share of biofuels in the economy and their potential to create jobs, it is possible to generate statistics on the input-output relationships. With the latter, we estimate a hybrid input-output model and calculate the effects of shocks on production and employment stemming from the full utilization of existing idle capacity, as well as from new investments in the sector. The instrument allows us to several policy evaluations, for instance, of acceleration of the energy matrix transition to renewables through regulations, to study the effect of changes in relative prices of energy, determine the effect on potential employment creation of subsidies to promote the activity, etc. The sector we analyze empirically had an initial value added of 745 million dollars and employs near to 1200 persons, and an important idle capacity plus delayed projects because of external shocks. In a conservative scenario of full capacity utilization plus ongoing investments, production more than doubles, and employment can grow 414 percent. On the other hand, a 50 percent additional increase in new capacity implies a total value-added increase of 421 million dollars and a 378 percent increase in jobs. Even when the output effect is lower than in the former scenario, the employment effect is proportionally much larger since the latter scenario includes transient jobs in the construction phase.